Millenarianism and Islamic Resurgence Exploring the Intertwining of Religious Belief and Politics in Contemporary Indonesia - Luthfi Makhasin (Review of Islam in Southeast Asia, 2018)
The current Islamic resurgence, simply defined as the return of Islamic beliefs, doctrines, and values as a sources of personal identification manifested in personal, political, cultural, and social life, poses positions Indonesian Muslims in the an enduring struggle to reconcile between religious tradition and modern life. Canonical traditions and classical Islamic texts that prophesied prophesy the imminent coming of YaumulQiyamah(Armageddon) and their popular reception among Indonesian Muslims reveal how religious texts still have a powerful influence in shaping the way Indonesian Muslims perceive the world and how they deal with it.This paper seeks to address continuing scholarly debate on the interconnection of Islamic tradition and modernity in contemporary Indonesia. It deals particularly with popular books on millenarian topics published in the last 15 years. Millenarian discourse on the imminent coming of Mahdi (the Savior) requires and implies that Muslims to be strongly committed to perform all religious obligations as prescribed in the Shariah (Islamic law). Millenarian discourse on the coming of Dajjal (the Deceiver) and the spread of Fitnah (Confusion) and Jahiliyya (Ignorance) has also becomes an ideological tools to make a demarcating line between Muslim-ness and Kafir-ness, and between the so-called dar Islam (House of Islam) and darHarb(House of Unbelievers).